2013
DOI: 10.1080/19443994.2013.792520
|View full text |Cite
|
Sign up to set email alerts
|

Advanced oxidation phenomena in electrocoagulation process: a myth or a reality?

Abstract: A B S T R A C TThis review discusses the advanced oxidation process (AOP) phenomena in electrocoagulation (EC) process. AOPs have been broadly defined as near ambient temperature treatment processes based on highly reactive radicals, especially the hydroxyl radical ð Á OHÞ as the primary oxidant. In principle, as water-containing colloidal particulates, oils, or other contaminants move through the applied electric field, there may be ionisation, electrolysis, hydrolysis, and free-radical formation which may al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 90 publications
(52 citation statements)
references
References 190 publications
0
51
0
Order By: Relevance
“…Moreover, Pt and boron-doped diamond (BDD) anodes are proved more convenient than other electrodes. Indeed, the great capability of a BDD anode to produce reactive oxygen species and other oxidising species during the electrolysis allows establishing a chlorine-free disinfection process [39]. Bergmann and Rollin [38] concluded that these electrochemical processes are very complex.…”
Section: Disinfection By-products (Dbps) Formation Risksmentioning
confidence: 99%
“…Moreover, Pt and boron-doped diamond (BDD) anodes are proved more convenient than other electrodes. Indeed, the great capability of a BDD anode to produce reactive oxygen species and other oxidising species during the electrolysis allows establishing a chlorine-free disinfection process [39]. Bergmann and Rollin [38] concluded that these electrochemical processes are very complex.…”
Section: Disinfection By-products (Dbps) Formation Risksmentioning
confidence: 99%
“…The removal efficiency was directly dependent upon the metal concentration in solution [23][24][25]. The positive metallic species were produced by the Al anode neutralising the negative charges on the polluting molecules [26][27][28][29][30].…”
Section: Ec Timementioning
confidence: 99%
“…The species Fe(OH) n(s) formed (by the two mechanisms) remained in the aqueous phase in the form of gelatinous suspension which can then remove the pollutants from the water (Figure 13), either by complexation, or by electrostatic attraction, followed by coagulation and flotation or sedimentation [24,25,27,28]. [27,28].…”
Section: Ec Using Fe Electrodesmentioning
confidence: 99%
See 1 more Smart Citation
“…This technology is particularly applicable in decentralized and rural areas because of its low infrastructure requirements, ease of use and potential for scalability [1,2]. While EC systems are often accompanied by supplementary treatment steps, including settling tanks and filters [3], the technology centers on applying an electric current to Fe(0) electrodes in contact with an electrolyte solution to promote the oxidative release of soluble Fe(II) ions [4,5]. The Fe(II) ions migrate from the Fe(0) anode surface to the bulk solution, where contaminant removal occurs by several possible pathways.…”
Section: Introductionmentioning
confidence: 99%